Comparative effects of organic and inorganic fertilizer treatment on growth, yield, and quality of lettuce (Lactuca sativa L.) - S. Afolabi, Michael; Salami, yodeji Ekundayo; Olajide, Olubunmi Olufunke; Babatunde, Fikayo Ezekiel (Journal of Pure and Applied Agriculture, 2023)
Lettuce (Lactuca sativa L.) is a very important exotic vegetable that can increase the income of farmers if high yield is obtained. However, high yield in Lactuca sativa is limited due to low soil fertility. The aim of this experiment is to evaluate the effect of organic and inorganic fertilizers on the growth, yield and quality parameters of lettuce. The experiment was laid out in a Randomized Complete Block Design (RCBD) with five treatments in three replications. The organic fertilizers used were poultry manure and cow dung applied at 40 ton/ha, while the inorganic fertilizer was NPK applied at 700 kg/ha and Urea applied at 200kg/ha. Data were recorded on five competitive plants for plant height (cm), leaf area (cm2 ). The data collected were subjected to analysis of variance (ANOVA). Comparison of means of yield parameters, its related characters and proximate analysis was also done using the same statistical package. The leaf yield (ton/ha) was also recorded. The results showed a high level of significance among the treatments, implying that the fertilizer used in this work affected the yield of Lactuca sativa and its related characteristics. Furthermore, high yield of Lactuca sativa were obtained from poultry manure (13.53 t/ha, 11.33 t/ha), cow dung (12.02 t/ha, 10.07 t/ha) and NPK (11.21 t/ha, 10.73 t/ha) in Igbon and Ejigbo, respectfully, while the least yield in both locations were obtained from control. The quality parameters showed that the treatments had no effect on the quality of Lactuca sativa. It is therefore concluded that poultry manure should be applied to lettuce to achieve higher yield while organic fertilizer should be applied to improve the quality. Also, lettuce should be harvested at 8 weeks after planting to avoid bitter taste. © 2021 Department of Agricultural Sciences, AIOU